2009
DOI: 10.1158/1078-0432.ccr-09-1044
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers Predict p53 Gene Therapy Efficacy in Recurrent Squamous Cell Carcinoma of the Head and Neck

Abstract: Purpose: Most recurrent squamous cell carcinomas of the head and neck have a dysfunctional p53 tumor suppressor pathway contributing to treatment resistance. We hypothesized that tumor p53 biomarkers may predict the efficacy of normal p53 delivered by gene therapy in these patients. Experimental Design: Tumor p53 biomarkers were evaluated in 116 patients, including 29 treated with methotrexate in a phase III randomized controlled trial. Profiles favorable for p53 gene therapy efficacy were hypothesized to have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
59
0
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(65 citation statements)
references
References 21 publications
(44 reference statements)
2
59
0
4
Order By: Relevance
“…Recent trials have shown success in patients with recurrent HNSCCs (38). Interestingly, tumors showing a TP53 mutation and lack of p53 expression by immunohistochemical staining had a higher chance of response when compared with tumors showing a mutation with expression of p53 (39). In the report of that study, no details on the type of TP53 mutation were described, but it is likely that the tumors without p53 expression are the ones that have a truncated TP53 mutation.…”
Section: Discussionmentioning
confidence: 93%
“…Recent trials have shown success in patients with recurrent HNSCCs (38). Interestingly, tumors showing a TP53 mutation and lack of p53 expression by immunohistochemical staining had a higher chance of response when compared with tumors showing a mutation with expression of p53 (39). In the report of that study, no details on the type of TP53 mutation were described, but it is likely that the tumors without p53 expression are the ones that have a truncated TP53 mutation.…”
Section: Discussionmentioning
confidence: 93%
“…Virus administration was performed by ultrasound-guided intratumoral or intracavitary (ovarian cancer, mesothelioma) injection, and one fifth of the dose was given i.v. The starting dose of 8 × 10 9 viral particles (VP) was chosen based on safety results published by others (1,(5)(6)(7)(8)(9)21). Subsequently, the dose was escalated to 1 × 10 , and 4 × 10 11 (Table 2).…”
Section: Treatment Protocolmentioning
confidence: 99%
“…Adenoviruses are among the most advanced cancer gene therapy platforms and their safety and efficacy has been validated in several randomized studies (6)(7)(8)(9). With regard to oncolytic adenoviruses, a few dozen trials have been performed and although there is anecdotal evidence of activity in most trials, overall single-agent efficacy has been nonimpressive.…”
Section: Introductionmentioning
confidence: 99%
“…Loss of heterozygosity 17p and mutations of the p53 have been detected in approximately half of all primary and most of recurrent cases of HNSCC (Nemunaitis et al, 2009;Gasco & Crook, 2003;Osman et al, 2002;Taylor et al, 1999). Studies of HNSCC and cell lines suggested that after mutation of one TP53 allele, the remaining wild-type allele is deleted and accordingly the mutant phenotype expressed (Nylander et al, 2000 as cited in Yin et al, 1999).…”
Section: Dysfunctions Of P53-mediated Apoptotic Pathway In Hnsccmentioning
confidence: 97%